223k views
4 votes
(3x² + x-2)(-4x2 - 2x - 1)

User Sastanin
by
4.9k points

1 Answer

2 votes

Answer

(3x² + x - 2) (-4x² - 2x - 1) = -12x⁴ - 10x³ + 3x² + 3x + 2

Step-by-step explanation

To expand this, we will use one of the two expressions to open the other one.

(3x² + x - 2) (-4x² - 2x - 1)

= 3x² (-4x² - 2x - 1) + x (-4x² - 2x - 1) - 2 (-4x² - 2x - 1)

= -12x⁴ - 6x³ - 3x² - 4x³ - 2x² - x + 8x² + 4x + 2

= -12x⁴ - 6x³ - 4x³ - 3x² - 2x² + 8x² - x + 4x + 2

= -12x⁴ - 10x³ + 3x² + 3x + 2

Hope this Helps!!!

User Woliveirajr
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.